Diversity and molecular characterization of novel hemoplasmas infecting wild rodents from different Brazilian biomes - Gonçalves, Luiz Ricardo [UNESP]; Roque, André Luiz Rodrigues; Matos, Carlos Antonio [UNESP]; Fernandes, Simone de Jesus [UNESP]; Olmos, Isabella Delamain Fernandez [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2015)
Although hemoplasma infection in domestic animals has been well documented, little is known about the prevalence and genetic diversity of these bacteria in wild rodents. The present work aimed to investigate the occurrence of hemotrophic mycoplasmas in wild rodents from five Brazilian biomes, assessing the 16S rRNA phylogenetic position of hemoplasma species by molecular approach. Spleen tissues were obtained from 500 rodents, comprising 52 different rodent species trapped between 2000 and 2011. DNA samples were submitted to previously described PCR protocols for amplifying Mycoplasma spp. based on 16S rRNA, followed by sequencing and phylogenetic inferences. Among 457 rodent spleen samples showing absence of inhibitors, 100 (21.9%) were PCR positive to Mycoplasma spp. The occurrence of hemotropic mycoplasmas among all sampled rodents was demonstrated in all five biomes and ranged from 9.3% (7/75) to 26.2% (38/145). The Blastn analysis showed that amplified sequences had a percentage of identity ranging from 86 to 99% with other murine hemoplasmas. The ML phylogenetic analysis of 16S rRNA gene of 24 positive randomly selected samples showed the presence of ten distinct groups, all clustering within the Mycoplasma haemofelis. The phylogenetic assessment suggests the circulation of novel hemoplasma species in rodents from different biomes in Brazil.
Keywords: Brazil; Hemotropic mycoplasmas; Molecular characterization; Wild rodents